Identifying Naturally Occurring Direct Assessments of Social-Emotional Competencies: The Promise and Limitations of Survey and Assessment Disengagement Metadata. (October 2019) - Soland, James; Zamarro, Gema; Cheng, Albert; Hitt, Collin
Social-emotional learning (SEL) is gaining increasing attention in education policy and practice due to growing evidence that related constructs are strongly predictive of long-term academic achievement and attainment. However, the work of educators to support SEL is hampered by a lack of available, unbiased measures of related competencies. In this study we conducted a literature review to investigate whether assessment metadata (typically data relevant to how students behave on a test or survey) can provide information on SEL constructs. Implications of this new source of SEL data for practice, policy, and research are discussed.